Linkages between dynamic phytoplankton C:N:P and the ocean carbon cycle under climate change - Matsumoto, K; Tanioka, T; Rickaby, R (Oceanography Society, 2020)
Modelers of global ocean biogeochemistry are beginning to represent a phenomenon that biologists have long observed in laboratory and field settings: that the elemental stoichiometry of phytoplankton is quite flexible. Today, it is well recognized that the C:N:P ratio in phytoplankton and particulate organic matter can vary substantially on ocean basin scales. Recent data show that, compared to the traditional Redfield ratio C:N:P = 106:16:1, the ratio is much higher in the oligotrophic subtropical gyres (~195:28:1) and much lower in eutrophic polar waters (~78:13:1). This pattern of variability, informed by results from phytoplankton incubation experiments, indicates that environmental factors such as nutrient availability and temperature are important drivers. Our model simulations of the global ocean carbon cycle under global warming and glacial conditions suggest that phytoplankton physiology and community composition control global C:N:P export. Model results also indicate the important role that Southern Ocean sea ice plays in determining the global export stoichiometry by altering the proportional contribution of Southern Ocean phytoplankton to global production. Sea ice retreat under warming and expansion under glaciation, while opposite in sign, can both elevate the global export C:N:P ratio by altering phytoplankton physiology and community composition in contrasting ways between each scenario. The global mean export C:N:P ratio increases from 113:16:1 in the control run to 119:17:1 by the year 2100 in the future run and to 140:16:1 in the glacial run. The impact of higher export C:N:P ratios is to strongly buffer carbon export against change for both scenarios.